1997
DOI: 10.1007/pl00005117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G protein-coupled receptors potently stimulating migration of human transitional-cell carcinoma cells

Abstract: The expression of G protein-coupled receptors inducing calcium mobilization and stimulating cell migration was examined in human transitional-cell carcinoma (J82) cells. Measurements of cytoplasmic Ca2+ concentration ([Ca2+]i) and phospholipase C activity indicated that these cells express several calcium-mobilizing receptors, including those for lysophosphatidic acid (LPA), thrombin, bradykinin, bombesin and histamine, of which only the LPA response was sensitive (approximately 50%) to pertussis toxin (PTX). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 35 publications
2
47
0
2
Order By: Relevance
“…For example, it was shown that AR triggers proliferation and TGFa induces invasion in cell lines derived from invasive transitional cancer tissue (De Boer et al, 1997). Little is known, however, about the function of GPCRs relating to bladder and kidney cancer with modest EGFR levels, although human transitional carcinoma cells express various GPCRs and display an enhanced migration rate in response to LPA and thrombin (Lummen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that AR triggers proliferation and TGFa induces invasion in cell lines derived from invasive transitional cancer tissue (De Boer et al, 1997). Little is known, however, about the function of GPCRs relating to bladder and kidney cancer with modest EGFR levels, although human transitional carcinoma cells express various GPCRs and display an enhanced migration rate in response to LPA and thrombin (Lummen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the precise mechanism, the pathway also is likely to be important in other aspects of fibroblast migration and chemotaxis (47,48). This pathway clearly differs from routine cell spreading and stress fiber formation, however, because fibroblasts were able to spread and form stress fibers on proteincoated surfaces under conditions that matrix contraction did not occur (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…LPA stimulation of fibroblast migration and chemotaxis was shown to depend on LPA receptors coupled to G i (44,45). On the other hand, LPA stimulation of stress fiber formation and focal adhesion assembly requires activation of the small G-protein Rho (29,30), a pertussis toxin-insensitive process (31) in which LPA receptors are coupled to G 13 (32).…”
Section: Discussionmentioning
confidence: 99%